Bilateral Necrotizing Fasciitis around the Hips Differentiated from Fournier Gangrene: A Case Report - Yang, Bo Kyu; Yi, Seung Rim; Lee, Ye Hyun; Kim, Hyun See; Nam, Seok Woo; Ahn, Young Joon; Kim, Seong Wan; Yang, Sung Wook; Im, Se Hyuk (Hip & pelvis, 2014)
As an emergency encountered in orthopedic practice requiring prompt diagnosis and aggressive treatment, necrotizing fasciitis around the hip must be discriminated from Fournier gangrene. The current case report describes a patient who suffered from bilateral type I necrotizing fasciitis around the hips, which was alleviated by prompt surgical debridement and intensive postoperative care.